Population, fear, and uncertainty : the global spread of fertility decline - Winter, J. M. (Yale University Press, 2013)
This eye-opening book looks at demographic trends in Europe North America, and Asia - areas that now have low fertility rates - and argues that there is an essential yet often neglected political dimension to a full assessment of these trends.